The Future of Freedom : Illiberal Democracy at Home and Abroad - Zakaria, Fareed (New York W.W. Norton & Company, 2003)
Examines the influence of democracy on politics, business and economics, law, culture, and religion in different regions of the world; explores the dark side of the democratic process; and reflects on the future of world democracy.
Include Notes and Index
Keywords: Political science--Philosophy -- Democracy -- Liberty